Flowering and fruiting phenology of Anaxagorea luzonensis A. Gray (Annonaceae) - DEWI AYU LESTARI; LINDA WIGE NINGRUM; MAFTUKHAKH HILMYA NADA; NARESVARA NIRCELA PRADIPTA; DIAN RAKHMAWATI HARSONO (Society for Indonesian Biodiversity, 2023)
Abstract. Lestari DA, Ningrum LW, Nada FMH, Pradipta NN, Harsono DR. 2023. Flowering and fruiting phenology of Anaxagorea luzonensis A. Gray (Annonaceae). Biodiversitas 24: 784-792. Anaxagorea luzonensis is one of the critical plant collections from the Annonaceae family, with only one specimen in Purwodadi Botanic Garden (PBG). In protecting these plants, it is necessary to know the process of flowering and fruiting through the phenological process. This research is expected to observe plant propagation, physiology, environmental response, and increased reproductive success. The aim of this research is to know the details of flowering and fruiting phenology stages, determine reproductive success, and explain the floral biology of A. luzonensis. Research on the flowering and fruiting phenology of A. luzonensis was carried out from December 2021 – November 2022 in one season at PBG. The method is observative, including changes in color, shape, and size of flowers and fruit in each phenological stage. In addition, the method includes the count of reproductive success and observation of the A. luzonensis flower. This study's results stated that the flowering and fruiting phenology of A. luzonensis experienced a shorter flowering time than fruiting time and a low percentage (<30%) of reproductive success. Flowering stages are divided into five stages, i.e. initiation, flower bud, before bloom, bloom, and anthesis; fruiting stages are divided into three stages, i.e. immature-sized, mature-sized, and ripe fruit, which occurred in period 73-121 ± 85 days. Environmental and genetic factors cause the low value of reproductive success. This research can be useful for the conservation strategy of A. luzonensis, especially for reproduction biology and seed conservation.